2014
DOI: 10.1108/imcs-05-2013-0032
|View full text |Cite
|
Sign up to set email alerts
|

An empirical investigation of the factors that influence Internet user’s ability to correctly identify a phishing website

Abstract: Purpose – The aim of this study is to report on the results of an empirical investigation of the various factors which have significant impacts on the Internet user’s ability to correctly identify a phishing website. Design/methodology/approach – The research participants were Internet users who have had at least some experience of financial transactions over the Internet. This study conducted a quantitative research with the help of a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 82 publications
1
23
1
Order By: Relevance
“…Usually phishing e-mails do not ask for a direct reply, but contain a link to a fraudulent website, which is 'the hook' in the fishing metaphor. This website is very similar in look and feel to the official website it impersonates (Alseadoon et al, 2012;Hinde, 2004;Purkait et al, 2014;. A recent report based on real-world online security incidents indicates that around 1 in 14 targets get successfully phished, either because they clicked the link or opened an attachment in a phishing e-mail (Verizon, 2017).…”
Section: Phishingmentioning
confidence: 89%
See 2 more Smart Citations
“…Usually phishing e-mails do not ask for a direct reply, but contain a link to a fraudulent website, which is 'the hook' in the fishing metaphor. This website is very similar in look and feel to the official website it impersonates (Alseadoon et al, 2012;Hinde, 2004;Purkait et al, 2014;. A recent report based on real-world online security incidents indicates that around 1 in 14 targets get successfully phished, either because they clicked the link or opened an attachment in a phishing e-mail (Verizon, 2017).…”
Section: Phishingmentioning
confidence: 89%
“…Successful phishing attacks often result in identity theft and subsequently in financial gains for the offender. However, Purkait et al (2014) stress the fact that money is not always the main objective for phishers. The collected information can also be used to harm the reputation of an individual or company, for example by spreading some controversial statements on behalf of another person.…”
Section: Phishingmentioning
confidence: 99%
See 1 more Smart Citation
“…Hunter (2006), in his article in Computer Fraud & Security, points out that although the day of the amateur hacker is gone, there are still plenty of amateur users. Researchers have found that security is not always the main concern for the user when they are online and submitting confidential login credentials into any website (Purkait, 2012b(Purkait, , 2014. Moreover, Internet users are lacking a baseline level of online safety awareness (Furnell, 2007), and they react to a variety of commonly available trust indicators such as logos, third-party endorsements and padlock icons over a selection of authentic phishing stimuli (Jakobsson et al, 2007).…”
Section: Related Workmentioning
confidence: 99%
“…On the one hand, there are users who are completely ignorant about phishing, and on the other hand, there are criminals who are developing new phishing ideas every day (Purkait, 2012). Researchers have studied in the past, why people fall for phishing attacks (Dhamija et al, 2006 andPurkait et al, 2014), or why people ignore security indicators provided by the anti-phishing toolbars of various Web browsers (Wu et al, 2006). However, there has been very little research on the effectiveness of these toolbars against fresh phishing sites or sophisticated DNS-based phishing attacks on local area networks (LANs).…”
Section: Introductionmentioning
confidence: 99%